KARAKTERISTIK PERIFITON PADA DAUN LAMUN MUDA DAN DAUN TUA Enhalus acoroides DI PERAIRAN PULAU KEDINDINGAN KOTA BONTANG KALIMANTAN TIMUR - Diana Nopita Sari; Aditya Irawan; Lily Inderia Sari (Jurnal Tropical Aquatic Sciences, 2022)
Seagrass sampling in this study was carried out using purposive sampling method at 4 research stations. The results of this study were found in 37 species of old seagrass leaves consisting of 9 classes, namely Bacillariophyceae, Mediophyceae, Coscinodiscophyceae, Euglenoidea, Cyanophyceae, Dinophyceae, Chorophyceae, Chrysophyta and Xexanauplia. While in young seagrass leaves there are 33 species consisting of 8 classes, namely Bacillariophyceae, Mediophyceae, Coscinodiscophyceae, Euglenoidea, Cyanophceae, Chrysophyta, Dinophyceae and Hexanauplia. The highest periphyton composition in old and young leaves was in the Bacillariophyceae class with a percentage of 67% on young leaves and 70.9% on old leaves. The diversity index value obtained showed moderate distribution criteria because the number of periphyton individuals found in old and young leaves was relatively the same.